1982
DOI: 10.3109/01485018208990214
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Antibodies in Serum and Semen in Men with Bilateral Congenital Absence of the Vas Deferens

Abstract: Sperm antibodies were evaluated in serum and semen of 14 cases with bilateral congenital absence of the vas deferens, by agglutination and complement dependent tests. The level of the various immunoglobulin fractions were determined by the single radial immuno diffusion method. Sperm agglutinins were present in serum in 71% of cases and in 29% in semen. Immunoglobin (Ig) M was not detected in semen of both patient and control groups, while IgG and IgA were absent in the semen of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Individuals with genital tract obstruction appear to be at an increased risk for anti-sperm antibodies (ASA), which are autoimmune antibodies against sperm cells. Elevated ASA titres have been found in 81% of men with obstruction as compared to 10% of men with other causes of infertility [35] , [36] , [37] . Once these antibodies are generated due to inoculation of the sperm antigens to the immune system, ASA will impair sperm motility, passage through the female reproductive tract, and will also affect the capacity for sperm to properly interact with the oocyte during fertilisation [38] .…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with genital tract obstruction appear to be at an increased risk for anti-sperm antibodies (ASA), which are autoimmune antibodies against sperm cells. Elevated ASA titres have been found in 81% of men with obstruction as compared to 10% of men with other causes of infertility [35] , [36] , [37] . Once these antibodies are generated due to inoculation of the sperm antigens to the immune system, ASA will impair sperm motility, passage through the female reproductive tract, and will also affect the capacity for sperm to properly interact with the oocyte during fertilisation [38] .…”
Section: Discussionmentioning
confidence: 99%
“…Their synthesis is like that of antibacterial antibodies [ 1,4,[6][7][8]: on the one hand, type-IgA SPZAA, the synthesis of which has been shown by several authors to occur in the glands' annex to the genital tract, with the predomi nant secretion in the prostate [10,14,17,18] (of these IgA, a part is synthesized in the form of secretory IgA), and on the other hand, type-IgG SPZAA, indicating humoral (general) involvement in the autoimmune reac tion [16,17], However, it seems that the occurrence of an anti-SPZ autoimmune reaction in the context of genital insult is a relatively rare phenomenon (14% positive for surface SPZAA in our study, between 3 and 20% in oth ers). This perhaps indicates that there exists a particular underlying immune situation which favors the appear ance of such a reaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, prior to 1989, only anecdotal cases of success with this approach for treatment of men with surgically unreconstructible reproductive tract obstruction had been reported [1], These men had congenital absence of the vas deferens (CAV) or multiple previous unsuccessful attempts at va sovasostomy or vasoepididymostomy. Previously pub lished reports suggested that these men had high levels of antisperm antibodies and would therefore be infertile even if sperm could somehow be retrieved from them [2,3], It was also thought that long-term obstruction of the reproductive tract would adversely affect testicular func tion for some of these men. Furthermore, recent evidence suggests that CAV has been shown to represent a mild reproductive form of cystic fibrosis and men with CAV have a significant chance of being heterozygous carriers for genetic abnormalities associated with cystic fibrosis [4].…”
Section: Introductionmentioning
confidence: 99%